PEMBELAJARAN AGAMA ISLAM YANG INTERAKTIF: Implementasi Metode Jigsaw Pada Materi Rukun Iman - Shofiyah, Siti; Amirsyah, Amirsyah; Sa’diyah, Rika; Karimah, Ummah; Fitriansyah, Mahliga; Fikriyah, Nur (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2025)
Interactive learning is very crucial because its implementation is still not optimal due to several factors. In addition, a teacher's skills are required to meet the current educational needs, one of which is the implementation of interactive learning. Not only general subjects, but also Religious Education, which involves doctrine, requires a pleasant learning process. The purpose of this research is to describe the application of the jigsaw method in cooperative learning of Islamic Religious Education on the subject of the Pillars of Faith. The research method used is descriptive qualitative research, and the data collection techniques used are observation and documentation. The research results show that the application of the jigsaw method in Islamic Religious Education on the material of the Pillars of Faith is very enjoyable and makes the learning process more interactive. The implication is that the enthusiasm and motivation to learn increased, and an improvement in learning outcomes is expected.